The decisive manager : get results, build morale, and be the boss your people deserve - Mitchell, Barbara, 1943-; Gamlem, Cornelia (Ascent Audio, 2023)
People issues. They seemingly arise out of nowhere and just don't go away. It's critical that managers handle them right. As a manager, you need to know so many things about managing people, but you don't even know what to ask! The Decisive Manager can help. With examples of typical situations that managers encounter and advice on how to handle them, it's an easy-to-use guide for people managers and has information on hiring to firing, and everything in between. You'll find information on: finding and hiring the best talent; creating a positive employee experience; paying and rewarding employees; helping employees grow and develop; understanding policies and practices; ensuring graceful endings; and the important issues surrounding remote and hybrid work. Concerned about navigating the changing workplace and avoiding legal pitfalls? There are questions and essential answers about these issues, too. Managing people correctly is critical to every manager's success. The Decisive Manager will help with those unexpected challenges that arise too often. This is a must-listen for all who lead.